2023
DOI: 10.3389/fpsyg.2023.1136351
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the intention of purchasing private pension scheme based on an integrated FBM-UTAUT model: The case of China

Abstract: The newly established private pension scheme in China has received great attention as it would be an important supplement to China’s social safety net and corporate annuity amid an aging population. It provides a way of helping to address the challenge of ensuring adequate retirement income, and the scheme is expected to grow significantly in the coming years. This study investigates factors affecting the intention of purchasing the private pension scheme using a conceptual model based on the integration of Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…Regression analysis will enable the identification of the variables that significantly affect the intention to adopt and use IMS [28,29]. It will be a use of a convenience sampling method to gather data from employees who use IMS in their daily work [30,31,32,33]. A power analysis will be conducted to determine the appropriate sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Regression analysis will enable the identification of the variables that significantly affect the intention to adopt and use IMS [28,29]. It will be a use of a convenience sampling method to gather data from employees who use IMS in their daily work [30,31,32,33]. A power analysis will be conducted to determine the appropriate sample size.…”
Section: Methodsmentioning
confidence: 99%
“…They found significant supporting evidence for all hypotheses: pension knowledge, perceived usefulness, perceived risk, and trust. Wu and Gong (2023) integrated the FBM and UTAUT models to construct a conceptual framework and investigated the determinants of the intention to purchase a private pension scheme in China. The research findings indicated that the two most influential factors are Effort Expectancy and Performance Expectancy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%